Quantitative Analysis of the Effect of Research and Development (R&D) Networks on Innovation and Competitive Advantage in Indonesia Case Studies in the Manufacturing Industry - Widalicin Januarty; Eva Yuniarti Utami; Badirun Basir; Eliagus Telaumbanua (North Press, 2024)
This research investigates the dynamic interplay between Research and Development (R&D) networks, innovation, and competitive advantage within the manufacturing sector of Indonesia through a quantitative analysis. A sample of 150 manufacturing firms participated in the study, providing valuable insights into the relationships among these critical variables. Confirmatory factor analysis ensured the validity and reliability of the survey instrument, and subsequent structural equation modelling uncovered direct effects and mediating mechanisms. The results reveal a significant positive impact of R&D network participation on both innovation and competitive advantage. Mediation analysis further illuminates the roles of knowledge transfer and collaboration intensity in shaping these relationships. The findings offer practical implications for policymakers and industry practitioners seeking to leverage R&D networks strategically. This study contributes to the growing body of knowledge on the dynamics of collaborative R&D efforts and their implications for innovation and competitiveness in the Indonesian manufacturing context.